Pengembangan kapasitas kelompok kerja tukang bangunan dalam membangun rumah sederhana tahan gempa di Kecamatan Muara Satu, Kota Lhokseumawe (Builder capacity development for build a simple earthquake resistant house in Muara Satu Sub-District, Lhokseumawe City) - Wesli, Wesli; Ersa, Nanda Savira; Widari, Lis Ayu (Universitas Syiah Kuala, 2022)
The purpose of this service is as an effort to improve the skills and social status and welfare of construction workers in Muara Satu Sub-District, Lhokseumawe City. Methods as well as provide basic education about how construction works in order to obtain information and understanding about simple earthquake-resistant house construction work. Stage while improving work group skills. builders in constructing building structures that meet the requirements of earthquake-resistant simple houses. The method of implementing the activity begins with site observation and licensing, participant recruitment and training implementation. To measure the success of the training, a pre-test and post-test were conducted in each material session. Based on the results of the activities that have been carried out, it is known that participants gain an increase in understanding of up to 40% after the training and are expected to be a provision for craftsmen in carrying out their profession. In conclusions, that the training went well and provided an increase in the knowledge of construction workers in terms of building simple earthquake-resistant houses. Partners must to understand the material provided in order to be a skilled builders.